Three-Month Follow-Up of the Post-COVID Syndrome after Admission to a Specialised Post-COVID Centre—A Prospective Study Focusing on Mental Health with Patient Reported Outcome Measures (PROMs) † - Schäfer, Isabel; Krehbiel, Johannes; Adler, Werner; Borho, Andrea; Herold, Regina; Greiner, Brigitte; Reuner, Miriam; Morawa, Eva; Erim, Yesim (International Journal of Environmental Research and Public Health, 2024)
Background and objective: The impairments and duration of PASC (post-acute sequelae of COVID-19) symptoms in mental health have, to date, not been comprehensively examined. Our objective is to provide longitudinal data on the mental health of Post-COVID patients and to identify risk and protective factors associated with a severe or prolonged course. Methods: The mental health of 265 Post-COVID patients of the outpatient Post-COVID centre of the University Hospital Erlangen was assessed 17.1 (T0) and 22.5 months after infection (T1). An online survey with validated questionnaires for Post-COVID symptoms (Post-COVID Syndrome Score), depression (Patient Health Questionnaire-9), somatic symptoms (Patient Health Questionnaire-15), anxiety (Generalized Anxiety Disorder-7), fatigue (Fatigue Severity Scale) and Post-Exertional Malaise (PEM) (DePaul Post-Exertional Malaise Screening) was conducted in the home environment. Results: In total, 80% of patients experienced severe PASC at follow-up. Clinically relevant symptoms of depression, persistent somatic symptoms, anxiety and fatigue were reported by 55.8%, 72.5%, 18.9% and 89.4% of patients, respectively. Depressive, anxiety and somatic symptom severity decreased significantly over time; fatigue and PEM remained at an unchanged high level. The risk factor for higher depression scores was older age; prior psychiatric illness treated with psychotherapy was associated with more severe depressive, somatic, anxiety and PASC symptoms. PEM symptoms were significantly associated with longer duration between acute infection and initial presentation in the Post-COVID centre. Conclusions: Our findings align with previous research, claiming severe mental health symptoms in PASC syndrome, lasting for months after infection. In-depth assessment of risk and protective factors for the mental health implications of PASC is needed for the planning of health services and disease prevention.
CRIS-Team Scopus Importer:2024-09-06
Keywords: long COVID; mental health; PASC; post-COVID syndrome; PROMs; psychological trajectory